Same but different: how agency modulates pain perception - Wiech, K (Cell Press, 2023)
Why is analgesic treatment more effective when it is self-administered? Strube et al. compare two possible accounts and show that the effect of agency on perception is linked to a shift in expectation (prior) rather than to reduced likelihood precision, highlighting that agency has a profound impact on the entire perceptual process.